Synthesis and Fungicidal Activity of Pyrazolecarboxamide Containing α-Aminoacetanilide Moiety - Zhi-Yong Fang; Hong Jiang; Xiao-Dong Ye (E-Journal of Chemistry)
A series of pyrazolecarboxamides containing α-aminoacetanilide moiety (4) were synthesized. These compounds were characterized by IR, MS and 1H NMR. Their fugicidal activities against Rhizoctonia solani, Sclerotinia sclerotiorum, Monilinia fructicola and Alternaria brassicae were evaluated. The results show that compound 4l and 4p, which bear only one electron-donating group on the para-position of phenyl or benzyl group, possessed excellent inhibitory activities against the above four fungi.